2010
DOI: 10.1242/jcs.075366
|View full text |Cite
|
Sign up to set email alerts
|

Cdc14p resets the competency of replication licensing by dephosphorylating multiple initiation proteins during mitotic exit in budding yeast

Abstract: SummaryIn eukaryotes, replication licensing is achieved through sequential loading of several replication-initiation proteins onto replication origins to form pre-replicative complexes (pre-RCs), and unscheduled replication licensing is prevented by cyclin-dependent kinases (CDKs) through inhibitory phosphorylations of multiple initiation proteins. It is known that CDK inactivation during mitotic exit promotes pre-RC formation for the next cell cycle. However, whether the removal of the inhibitory phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 53 publications
5
50
0
3
Order By: Relevance
“…p1ARS contains one replication origin ARS1, and p8ARSs carries seven additional copies of H4-ARS inserted into p1ARS. It has been well documented that all known replication initiation mutants have a higher rate of p1ARS loss compared with p8ARSs (Hogan and Koshland, 1992;Loo et al, 1995;Zhang et al, 2002;Cheng et al, 2010;Ma et al, 2010;Wang et al, 2010;Zhai et al, 2010). In control cells containing the empty BD vector, the loss rates of p1ARS and p8ARSs were 1.2% and 0.5% per generation, respectively (Fig.…”
Section: Cdt1p and Mcm6p Interact Through Their C-terminal Domainsmentioning
confidence: 80%
“…p1ARS contains one replication origin ARS1, and p8ARSs carries seven additional copies of H4-ARS inserted into p1ARS. It has been well documented that all known replication initiation mutants have a higher rate of p1ARS loss compared with p8ARSs (Hogan and Koshland, 1992;Loo et al, 1995;Zhang et al, 2002;Cheng et al, 2010;Ma et al, 2010;Wang et al, 2010;Zhai et al, 2010). In control cells containing the empty BD vector, the loss rates of p1ARS and p8ARSs were 1.2% and 0.5% per generation, respectively (Fig.…”
Section: Cdt1p and Mcm6p Interact Through Their C-terminal Domainsmentioning
confidence: 80%
“…Altogether, these events promote pre-RC assembly in a step-wise manner onto replication origins for replication initiation. Phosphorylated, inactive Cdc14p substrates are shaded gray, while their dephosphorylated, active forms are highlighted in red (substrates identified by us in Zhai et al, 2010) or orange (previously identified substrates). Modified from Zhai et al, 2010.…”
Section: Proposed Model Of Cdc14p-driven Origin Licensingmentioning
confidence: 99%
“…27 In fact, we identified several additional idr mutants in CDC14 from the tertiary screen and further found that the phosphatase Cdc14p indeed plays an essential role in replication initiation by directly dephosphorylating several replication initiation proteins. 31 The idr mutants that could not be rescued by any of the known IDR genes were then transformed with a yeast genomic library 32 in order to clone the candidate IDR genes by complementation of the p1ARS plasmid loss phenotypes. Two methods were used to identify colonies containing the complementing library plasmids.…”
Section: Tables 1-4)mentioning
confidence: 99%
“…To further examine the genetic interactions of CTF1 and CTF18 with replication related genes, we utilized a genetic assay, synthetic dosage lethality, 31,40,41 to test cell growth defects in ctf1 and ctf18 mutants upon overexpression of individual known replication related genes, ORC1-6, MCM2-7, CDT1, CDC7, DBF4, CDC45, SLD2, SLD3, DPB11 and POL12. The results (see summary on Table 2 and data examples in Fig.…”
Section: Tables 1-4)mentioning
confidence: 99%